Benefits of cannabidiol in the treatment of children with autism: a review of effects on behavior and quality of life - Silva Junior, Agnaldo Marcelino da; Guimarães, Mônica Soares de Araújo; Silva, Juliana Lilis da; Amâncio, Natália de Fátima Gonçalves (JRG Journal of Academic Studies, 2024)
Autism Spectrum Disorder (ASD) is a neuropsychiatric condition characterized by deficits in communication and social interaction, often associated with comorbidities such as anxiety and sleep disorders. Conventional treatments have limitations, encouraging the search for alternative therapies. The objective of the study is to review the scientific literature to evaluate the effects of cannabidiol in the management of behavioral symptoms and in improving the quality of life of children with ASD. An integrative methodology, guided by the PICO strategy, was used, with searches in PubMed, SciELO and other databases, including studies published between 2020 and 2024. Twenty-three articles were selected after inclusion and exclusion criteria. The results demonstrate that CBD can reduce symptoms such as irritability, aggression and hyperactivity, in addition to promoting improvements in sleep disorders and social interaction. A positive impact on the quality of life of children and their families was also observed. However, the efficacy of CBD in the core symptoms of ASD, such as communication difficulties, is still limited. Studies suggest that side effects are minimal, but long-term safety remains uncertain. In conclusion, CBD has promising benefits as an adjunctive therapy for ASD, especially in alleviating behavioral symptoms and associated comorbidities. However, the lack of robust evidence prevents its definitive recommendation. Additional research is needed to confirm its efficacy and safety, especially in pediatric populations, and to establish appropriate clinical protocols.